Strain tuned magnetocrystalline anisotropy in ferromagnetic H-FeCl2 monolayer. (March 2018) - Zheng, Huiling; Han, Hecheng; Zheng, Jun; Yan, Yu
Abstract: For the utilization of two-dimensional materials with ferromagnetism in high density storage, it is very important to find an effective method to enhance their perpendicular magnetocrystalline anisotropy. In this paper, we investigated the impact of strain on structure and magnetism of the H-FeCl2 monolayer by employing first-principles calculations. Our results show that stressless H-FeCl2 monolayer not only is dynamically stable, but also has intrinsic ferromagnetism and perpendicular magnetocrystalline anisotropy. Under the strains ranging from −3% to 3%, the structure of the H-FeCl2 monolayer is always dynamically stable and its ground state is always ferromagnetic (FM) configuration. Interestingly, applying compressive strain can enhance the FM. More importantly, we found the compressive strain can enhance the perpendicular magnetocrystalline anisotropy of H-FeCl2 monolayer by 20.9%. Contrarily, tensile strian can make the perpendicular magnetocrystalline anisotropy decrease by 14.5%. The analysis of density of state (DOS) and the dedications to magnetocrystalline anisotropy energy (MAE) of 3d orbitals of Fe atom demonstrate that the comepressive (tensile) strain influence depends on the decrease (increase) of the negative part to MAE from the hybridization between 3 d y z and 3 d z 2 states through spin-orbit coupling interaction. Our study indicates that applying compressive strain can effectively enhance the ferromagnetism and perpendicular magnetocrystalline anisotropy of H-FeCl2 monolayer for its application in high density data storage. Highlights: Unstrained H-FeCl2 monolayer has intrinsic ferromagnetism and perpendicular magnetocrystalline anisotropy. Under the strains ranging from −3% to 3%, the structure of the H-FeCl2 monolayer is still dynamically stable. Compressive strain can enhance the perpendicular magnetocrystalline anisotropy in theH-FeCl2 monolayer.